THE ROLE OF STRATEGIC CHANGES RELATED TO INNOVATION, COMPETITION AND TECHNOLOGY IN UZBEKISTAN - Mirzayev Laziz Tulkinovich (European Science Publishing, 2025)
In a rapidly evolving global landscape, Uzbekistan stands at a crucial juncture where strategic changes in innovation, competition, and technology are imperative for sustainable development. As the nation seeks to strengthen its economic foundation and enhance its global standing, understanding the role of these strategic shifts becomes essential.
Keywords: Innovation, competition, strategies, economy, technology